Proton therapy in the treatment of hepatocellular carcinoma - Dionisi, Francesco; Scartoni, Daniele; Fracchiolla, Francesco; Giacomelli, Irene; Siniscalchi, Benedetta; Goanta, Lucia; Cianchetti, Marco; Sanguineti, Giuseppe; Brolese, Alberto (Frontiers in Oncology, 2022)
Liver cancer represents one of the most the most common cause of death from cancer worldwide. Hepatocellular carcinoma (HCC) accounts for 90% of all primary liver cancers. Among local therapies, evidence regarding the use of radiation therapy is growing. Proton therapy currently represents the most advanced radiation therapy technique with unique physical properties which fit well with liver irradiation. Here in this review we aim to 1) illustrate the rationale of use of PT in the treatment of HCC, 2) discuss the technical challenges of advanced PT in this disease, 3) review the major clinical studies regarding the use of PT for HCC, 4) analyze the potential developments and future directions of PT in this setting.